ISLAMIC ETHICS EDUCATION CONCEPT FOR GEN Z: IBN MISKAWAYH’S VIEW ON PHILOSOPHY - Yetty Faridatul Ulfah; Alfian Eko Rochmawan; Faruq Alhasbi (Universitas Muhammadiyah Surakarta, 2024)
The prevalence of an ethical crisis among young people reflects their moral decay. Therefore, it is imperative to teach ethics education to the next generation of this nation. This research aims to investigate the concept of Islamic ethics education for Generation Z from the perspective of one of the renowned Muslim philosophers, Ibn Miskawaih, also known as the Father of Islamic Ethics. The research methodology involved the use of library resources. The primary reference is Ibn Miskawaih's Tahdzib Al Akhlak, with additional sources utilized to assess Islamic ethics and Generation Z. The findings of this study demonstrate that Ibn Miskawaih examines the ethical notion of right and wrong conduct based on logical reasoning. It is imperative to instil Islamic ethics in Generation Z to cultivate virtuous behaviour, courteousness, and sagacity.